Manajemen Pengelolaan Kelas di PAUD Al-Basyir Desa Tanjung Baru - Anisa Fitri; Ade Akhmad Saputra (Pendidikan Al-Gafari, 2024)
The purpose of this research is to describe the implementation of classroom management in PAUD Al-Basyir, Tanjung Baru Village. Improper classroom management will affect the learning process. Inappropriate classroom management often occurs because no effort is made in creating and maintaining optimal classroom conditions in the learning process. The research conducted used a qualitative approach. In this study using several methods, namely interview, observation, and documentation methods. From the research conducted obtained the results that in PAUD Al-Basyir Tanjung Baru for the management of the class has been good in its management as well as the first laying of tools or learning media in accordance with the needs of its activities. Second, the arrangement of tables and chairs is appropriate which is given a distance to make it easier for students to interact with each other. Third, the position of toys is arranged in such a way as to adjust their function and toy storage is placed in a position that is easily accessible to children, making it easier for children to practice independently when returning toys that have been used. Fourth, children are given the freedom to imagine in the creativity that is placed on the classroom wall. Fifth, for the management of the class, more attention should be paid so that children are not bored during the learning process and finally it is hoped that in the classroom there is air ventilation so as toproduce air exchange in the classroom